ANALISIS KONSTANTA LAJU PENGERINGAN DAN KARAKTER SIMPLISIA BUNGA KAMILEN (Matricaria chamomilla L.) DENGAN BEBERAPA METODE PENGERINGAN - Devi Safrina; Dian Susanti; Arsy Nurul Khotimah (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Chamomile (Matricaria chamomilla L.) is a plant that people widely use in traditional medicine. Chamomile parts used as medicine are the flower, usually dried before use, commonly named simplicia. Several drying methods can be used and closely relate to the resulting simplicia character. One of the simplicia characteristics observed is organoleptic (shape, color, and scent). The difference in the drying method used also causes variations in the moisture content of the simplicia. The drying process for an extended period can damage the content of Chamomile flowers. To overcome this, an analysis is needed to predict drying time to comply with established standards. One indicator to predict drying time is to determine the value of the drying rate constant (k). This study aims to obtain the value of the drying rate constant by several drying methods and their effects on the organoleptic character of simplicia (shape, color, scent). The research uses five drying methods, and three repetitions include drying by wind, indirect sunlight, sunlight, and oven combination, oven drying using silica gel, and oven drying without silica gel. Results showed that the drying method significantly affected the rate of drying constantly. The highest drying rate constant was reached by oven drying with silica gel at 0.5758 days-1 and oven drying without silica gel at 0.5751 days-1. The drying method did not significantly influence the shape, color, and scent of chamomile simplicia.